TikTok Effect to Develop Students’ Motivation in Speaking Ability - Jenni Ferstephanie; Theodesia Lady Pratiwi (English Education : English Journal for Teaching and Learning, 2021)
The study was conducted to explore the effect of TikTok in developing the students’ motivation in speaking. The study was conducted through Classroom Action Research. The involved participants were 25 students from the tenth grade of SMA Kristen Kalam Kudus, Selatpanjang. The study used qualitative and quantitative methods in collecting the data. The research procedures were planned in organized procedures as mentioned: planning, implementing, observation and reflection. The research instruments were questionnaire, pre-test, and post-test. The questionnaire was designed into Likert scale format. Then, the pre-test and post-test were implemented in the study. The post-test took two cycles. The research findings identified that the students’ motivation level was at a moderate level 3.84. However, the post-test showed that the students’ scores rapidly increased and were better than their pre-test. Therefore, the implementation of TikTok proved that it was effective to develop students’ motivation in speaking ability. In conclusion, TikTok application engaged the students to enjoy the learning especially in motivating them to speak. Students were free to express their ideas while making the content.